2015
DOI: 10.11622/smedj.2016104
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients who made a return visit within 72 hours to the emergency department of a Singapore tertiary hospital

Abstract: INTRODUCTION 72-hour emergency department (ED) reattendance is a widely-used quality indicator for quality of care and patient safety. It is generally assumed that patients who return within 72 hours of ED discharge (72-hour re-attendees) received inadequate treatment or evaluation. The current literature also suggests considerable variation in probable causes of 72-hour ED reattendances internationally. This study aimed to understand the characteristics of these patients at the ED of a Singapore tertiary hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 17 publications
(30 reference statements)
4
33
0
2
Order By: Relevance
“…A previous study forms the basis for this classification because ED revisit was found to be common in the population aged ≥60+ years. 10 A new patient was defined as the first presentation of an individual to receive ED services.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study forms the basis for this classification because ED revisit was found to be common in the population aged ≥60+ years. 10 A new patient was defined as the first presentation of an individual to receive ED services.…”
Section: Methodsmentioning
confidence: 99%
“…The ED revisit within 72 hours has been widely reported in earlier studies, and its rate depends on the chronic disease status and the cultural background. 6 12 The rates of 72-hour ED revisits may depend on age, 10 , 11 gender, 10 , 13 disease categories, 6 – 8 , 12 medical errors, 7 , 8 patients, 7 and doctors. 7 Although data regarding ED revisits within 72 hours can be used to implement changes and modifications to improve the electronic medical record database, the rate of revisits to the ED within 72 hours has not been documented among adults with chronic diseases in Saudi Arabia, particularly in our center.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may reflect certain risk factors for our participant group, in particular being male and arriving by ambulance, previously associated with ED re‐presentation within a short period (Chan et al . 2016). Using another indicator of possible hospital care failings was that for 46% of participants and 59% of the re‐presentations, subsequent presentations occurred within 30 days, which was higher than for male ID patients reported by Kelly et al .…”
Section: Discussionmentioning
confidence: 99%
“…Results of a Singapore study, however, indicated the following risk factors for a 72h ED return: arriving by ambulance, male gender, older age, nonambulant with a major emergency triage, and diagnosis of cardiac problems, abdominal pain or viral infection, and Chinese ethnicity (Chan et al . 2016). A return within 30 days has been an indicator of preventable hospital presentation (Kelly et al .…”
Section: Introductionmentioning
confidence: 99%
“…Readmissões dentro de 72 horas na unidade de emergência são amplamente utilizadas como indicador de qualidade da assistência e segurança do paciente, uma vez que estão associadas aos erros de avaliação médica e ao estabelecimento de tratamentos inadequados (BENBASSAT;TARAGIN, 2000). Estudos avaliaram as características clínicas de pacientes readmitidos e constataram que idosos, portadores de doenças cardíacas, abdominais e virais, bem como pacientes classificados como graves no momento da triagem inicial estavam mais propensos a retornar à unidade emergência após três dias da alta hospitalar (CHAN et al, 2016;MAGDELIJNS et al, 2016). As estatísticas mostraram que 42% dos pacientes relataram novas queixas e 24% foram readmitidos devido a exacerbação ou piora dos sintomas relatados na visita anterior (HEITMANN et al, 2016).…”
Section: Relação Entre Registros Da Pressão Arterial E Indicadores Deunclassified